IMPERATIVES IN KEO LANGUAGE: A STUDY OF SOCIOLINGUISTICS - Soo, Maria A; Roni, Marianus; Doi, Maksimilianus (Lantern: Journal of Language and Literature, 2022)
Imperative sentence is a sentence that request the person we are speaking with to do or not to something. Imperative is also found in local language like Keo language. The purpose of this study was to find out the types and functions of imperative found in Keo language used by Uluwagha community in daily conversation using the theory of Hornby (1976) and to analyze about imperative sentence adopted the method issued by Dorney 2007. The study used descriptive qualitative. There were some steps that the writer used to analyze the data. First step was interviewing the informants who were native speakers of Keo language. The second was to translate imperative sentences into Keo language in English and the last was to make the conclusion. The results of the study show that there are two types and six functions of imperative found in Keo language. They are positive and negative imperatives.